If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3 = 0.28 Reorder the terms: -3 + x = 0.28 Solving -3 + x = 0.28 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = 0.28 + 3 Combine like terms: -3 + 3 = 0 0 + x = 0.28 + 3 x = 0.28 + 3 Combine like terms: 0.28 + 3 = 3.28 x = 3.28 Simplifying x = 3.28
| x=224000-0.5(202000-0.5x) | | y=32-14x | | 17x+9y=4 | | x=32-14-y | | 3x+5-3x+6+7x=9-2x+5+9x | | 10m+2p=42 | | -7-3(1-9f)=31 | | 5(f-5)=-3.5 | | -8(s+3)=4 | | y+7(2)=2 | | y+3(-3)=2 | | 6(3s+10)=276 | | Xx(x+1)=272 | | 14+x+y=32 | | 5x+2-3=6x+4 | | 4(a-10)=32 | | 3(7r-5)=6(6r+5) | | (u+2)*7=35 | | 10x+5(x-3)=2x+15 | | 14x+y=32 | | (q-4)*4=36 | | -5(2t+7)=-5 | | 12x-3x+x=5x-4+8x | | 5x-12=-3x+20 | | 2(f-3)=6 | | 1-2x+3x^2=0 | | 8(s-4)=-100 | | j=(2c-6)(6c+6)-2(4c-2) | | c=2*150+2 | | 6(3s+3)=180 | | 3(3s-4)=2(4s+4) | | 2(2l+5)=54 |